2005
DOI: 10.1002/pola.21193
|View full text |Cite
|
Sign up to set email alerts
|

Sol–gel transition behavior of biodegradable three‐arm and four‐arm star‐shaped PLGA–PEG block copolymer aqueous solution

Abstract: Two types of temperature‐sensitive biodegradable three‐arm and four‐arm star‐shaped poly(DL‐lactic acid‐co‐glycolic acid‐b‐ethylene glycol) (3‐arm and 4‐arm PLGA–PEG) were successfully synthesized via the coupling reaction of 3‐arm and 4‐arm PLGA and α‐monocarboxyl‐ω‐monomethoxypoly(ethylene glycol) (CMPEG). In dilute aqueous solutions, star PLGA–PEGs showed the temperature‐ and concentration‐dependent formation and aggregation of micelles over specific concentration and specific temperature. With increasing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…As shown in Figure 3D, the T g of the 3S-PLGA was about 50.91°C, while 3S-PLGA-PEG was 47.5°C. The results showed that the T g of 3S-PLGA-PEG was lower than 3S-PLGA because the existence of PEG can affect the crystalline property of PLGA, which can reduce the T g of this polymer, 33,34 and suggested the PEG segment was linked with PLGA.…”
Section: Characterization Of Micelles Critical Micelle-concentration mentioning
confidence: 96%
“…As shown in Figure 3D, the T g of the 3S-PLGA was about 50.91°C, while 3S-PLGA-PEG was 47.5°C. The results showed that the T g of 3S-PLGA-PEG was lower than 3S-PLGA because the existence of PEG can affect the crystalline property of PLGA, which can reduce the T g of this polymer, 33,34 and suggested the PEG segment was linked with PLGA.…”
Section: Characterization Of Micelles Critical Micelle-concentration mentioning
confidence: 96%
“…So, in the latter case, micelles with the hydrophobic PLGA core (black line) and the hydrophilic dangling free PEG ends (red lines) are formed and these micelles (grey dotted line) aggregate like lipid-layer structure without connections between micelles as we suggested in the previous paper. 17 However, in the former case, PLGA blocks at the end of each star polymer can be easily located in the center of different micelles having four arm PEG acting as bridges connecting each micelle. These bridges make 4arm PEG-PLGA in an aqueous solution form continuous networks and have a lower CGC than 4arm PLGA-PEG.…”
Section: Sol-gel Transitionmentioning
confidence: 99%
“…We also developed biodegradable three-arm and four-arm star-shaped PLGA-PEG block copolymers (3arm PLGA-PEG and 4arm PLGA-PEG) with PEG having fixed molecular weight of 550 and observed their sol-gel-sol transition in high concentration regions (above 24 wt %). 17 Recently, we synthesized and characterized biodegradable four-arm star-shaped PEG-PLGA block copolymers (4arm PEG-PLGA) with the reverse molecular structure to 4arm PLGA-PEG to study the effect of the structure on gelation behavior in star-shaped block copolymers. The molecular weight of 4arm PEG was fixed and the molecular weight and the mole ratio of DL-lactide to glycolide of PLGA block were varied by the feed mole ratios of DL-lactide, glycolide, and 4arm PEG.…”
mentioning
confidence: 99%
“…It is observed that micelle formation is not just concentration dependent but also depends on the temperature. The rheological studies on aqueous solutions of the block copolymer reveal a weak gel to sol transition across the LCST different from the existing reports [31][32][33]. In the polymer concentrations investigated, the solution flows, yet manifested solid like behavior with G′ > G″ with the modulus being frequency dependent and the magnitude of G′ is two-fold higher than G″ which implies a weak gel state.…”
mentioning
confidence: 52%